2015
DOI: 10.1177/1089253215573327
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Blood Ordering Process for Cardiac Surgical Cases Using an Institution-Specific Version of the Maximum Surgical Blood Order Schedule

Abstract: Using the gold standard C:tx of >2:1 as an indicator of inappropriate blood utilization, our analysis confirmed that excessive crossmatching occurred for several procedures. Now a subset of cardiac surgical cases only requires a type and screen order prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Recently, programmed implementation of more restrictive transfusion policies, such as Patient Blood Management (PBM) [28] and Maximum Surgical Blood Order Schedule (MSBOS), would result in a significant reduction in overall consumption of red cells. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, programmed implementation of more restrictive transfusion policies, such as Patient Blood Management (PBM) [28] and Maximum Surgical Blood Order Schedule (MSBOS), would result in a significant reduction in overall consumption of red cells. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Tabela 5-Análise do índice de pacientes transfundidos nos procedimentos cirúrgicos realizados no Hospital Ophir Loyola. Estudos sugerem a realização de compatibilização de pelo menos dois concentrados de hemácias (Ural et al, 2016;Moghaddamahmadi et al, 2021), de fato, notou-se, que a maioria dos procedimentos realizados no hospital necessita de cerca de dois concentrados de hemácias (Figura 5). Acredita-se, ainda, que a perda média estimada de sangue na maioria dos procedimentos cirúrgicos seja de 100-600 mL (Sharingcarinkul & Chuasuwan, 2018), o que corresponde em média a um volume comportado normalmente por um a dois concentrados de hemácias.…”
Section: Patologiaunclassified
“…However, recent studies have indicated that about 50% of people undergoing cardiac surgery did not receive any blood units. 5 …”
Section: Introductionmentioning
confidence: 99%